Chemically induced phenotypes during the blood stage development of Plasmodium falciparum as indicators of the drug mode of action - Reghunandanan, Keerthy; Chandramohanadas, Rajesh (Frontiers in Drug Discovery, 2022)
Malaria remains a health and economic burden, particularly in marginalized populations worldwide. The current strategies for combating malaria rely on eliminating the mosquito vector, using insecticide-treated nets, and other management policies or through the administration of small molecule drugs to perturb the intra-erythrocytic development of the parasite. However, resistance against commonly used drugs such as artemisinin has recently become a concern necessitating the identification of novel pharmacophores with unique mechanisms of action. This review summarizes the various life-stage events of the malaria parasite, Plasmodium falciparum, during the in vitro development, which can be targeted by different classes of small molecules. We also describe various chemically induced phenotypes and methods to ascertain and validate drug-induced changes to derive early insights into which cellular mechanisms are affected.